A new frog of the genus Pristimantis (Amphibia: Strabomantidae) from the high Andes of Southeastern Ecuador, discovered using morphological and molecular data - Arteaga-Navarro, Alejando (2011)
We describe a new small sized (SVL in females ≤ 25.7 mm; in males, ≤20.1 mm) Pristimantis, associated with bamboodominated forests in the Reserva Mazar, Andes of Southeastern Ecuador, at elevations between 2876-2989 m. This species is assigned to the P. orestes group, from whose members it differs by the absence of tubercles on heel and outer edge of tarsus, lacking a discoidal fold, presence of slightly expanded finger and toe pads, and bright yellow blotches on groi , axilla and anterior surfaces of thigh. The advertisement call of the new species consists of a series of short, indistinctly pulsed notes, and has a dominant frequency of 2.50-2.56 kHz. A molecular phylogeny based on a fragment of the mitochondrial gene 12S shows that the new species is sister to a clade formed by Pristimantis simonbolivari and an undescribed Pristimantis. © 2011 Magnolia Press.